Вы находитесь на странице: 1из 4

# EUM114 PDE

## Wave Equation, Stretched String Problem with given Initial Displacement

An elastic string is stretched and fixed at two points 20 m apart. The centre of the string is displaced
vertically 1 m upward from its rest position, and then released with initial zero velocity. The
displacement u(x,t) follows wave equation. Given c = 1, obtain the solution for this problem.

Simple Sketching:

## u(x,0) Initial Displacement, at time t = 0

x
0 10 20

Solution:

𝜕2 𝑢 𝜕2 𝑢
Wave equation: = 𝑐2 (1)
𝜕𝑡 2 𝜕𝑥 2

## Assuming the PDE is separable, 𝑢(𝑥, 𝑡) = 𝑋(𝑥)𝑇(𝑡)

𝜕2 𝑢 𝜕2 𝑇 𝜕2 𝑢 𝜕2 𝑋
Then =𝑋 and =𝑇
𝜕𝑡 2 𝜕𝑡 2 𝜕𝑥 2 𝜕𝑥 2

𝜕2 𝑇 𝜕2 𝑋
Into (1) gives 𝑋 = 𝑐2𝑇
𝜕𝑡 2 𝜕𝑥 2
1 𝜕2 𝑇 1 𝜕2 𝑋
Rearrange = =  (separation constant)
𝑐 2 𝑇 𝜕𝑡 2 𝑋 𝜕𝑥 2

Three cases for separation constant ( > 0,  = 0,  < 0) will yield 3 different solutions.

Only  < 0 will yield useful solution, hence use  = −𝑘 2 , for any real value k provided k  0.

1 d2 𝑋 1 d2 𝑇
ODE1 = −𝑘 2 ODE2 = −𝑘 2
𝑋 d𝑥 2 𝑐 2 𝑇 d𝑡 2
d2 𝑋 d2 𝑇
+ 𝑘 2 𝑋=0 + 𝑘2𝑐2𝑇
=0
d𝑥 2 d𝑡 2
Which is a second order ODE with complex roots: Which is again a second order ODE with complex
m = 0 ± ki roots:
Which give solution: m = 0 ± kci
𝑋 = 𝑐1 cos 𝑘𝑥 + 𝑐2 sin 𝑘𝑥 Which give solution:
𝑇 = 𝑐3 cos 𝑘𝑐𝑡 + 𝑐4 sin 𝑘𝑐𝑡

The general solution (GS) for this problem can be formulated as a product of 2 functions:
𝑢(𝑥, 𝑡) = (𝑐1 cos 𝑘𝑥 + 𝑐2 sin 𝑘𝑥)(𝑐3 cos 𝑘𝑐𝑡 + 𝑐4 sin 𝑘𝑐𝑡) (2)
Given c = 1, the GS becomes:
𝑢(𝑥, 𝑡) = (𝑐1 cos 𝑘𝑥 + 𝑐2 sin 𝑘𝑥)(𝑐3 cos 𝑘𝑡 + 𝑐4 sin 𝑘𝑡) (3)

Expected 4 conditions to solve for arbitrary constants c1, c2, c3 and c4.

## Boundary conditions (BCs) due to 2 fixed points separated 20 m apart (L = 20):

(1) BC1: u(0,t) = 0 (t  0)
(2) BC2: u(L,t) = 0 (t  0)

## Initial conditions (ICs) at time t = 0 for 0  x  20

(3) IC1: u(10,0) = 1 (displacement at the centre of the string, *need expression at any point)
𝜕𝑢
(4) IC2: (𝑥, 0) = 0 (initial velocity of the string at any point)
𝜕𝑡

## Applying BC1 into (3) gives:

0 = 𝑐1 (𝑐3 cos 𝑘𝑡 + 𝑐4 sin 𝑘𝑡)
This implies that c1 = 0 since the term (𝑐3 cos 𝑘𝑡 + 𝑐4 sin 𝑘𝑡) cannot be always zero due to varying time t.

## GS from (3) is reduced to:

𝑢(𝑥, 𝑡) = 𝑐2 (sin 𝑘𝑥)(𝑐3 cos 𝑘𝑡 + 𝑐4 sin 𝑘𝑡) (4)

## Applying BC2 into (4) gives:

0 = 𝑐2 (𝑠𝑖𝑛 𝑘𝐿)(𝑐3 cos 𝑘𝑡 + 𝑐4 sin 𝑘𝑡)

This implies that sin kL = 0, since c2  0 and again (𝑐3 cos 𝑘𝑡 + 𝑐4 sin 𝑘𝑡) cannot be always zero.

## Hence sin 𝑘𝐿 = 0 = sin 𝑛𝜋

𝑛𝜋
𝑘= n = 1, 2, 3, …
𝐿

Knowing the value of k, we still have c2, c3 and c4 to find. Applying IC1 at this stage won’t reduce the GS, so we
will use IC1 later. To apply IC2, we need to partially differentiate equation (4) w.r.t. t:
𝜕𝑢
= 𝑐2 (𝑠𝑖𝑛 𝑘𝑥)(−𝑐3 sin 𝑘𝑡 + 𝑐4 cos 𝑘𝑡)
𝜕𝑡
Applying IC2 to the above equation gives:
0 = 𝑐2 (sin 𝑘𝑥)(𝑐4 )
Since c2  0 and also sin kx not always zero at varying locations, this implies that c4 = 0.

## Therefore GS from (4) is reduced to:

𝑢(𝑥, 𝑡) = 𝑐2 (𝑠𝑖𝑛 𝑘𝑥)(𝑐3 cos 𝑘𝑡) (5)

Re-writing the above equation by substituting the value of k and introducing bn = c2c3 for specific value of n:
𝑛𝜋𝑥 𝑛𝜋𝑡
𝑢(𝑥, 𝑡) = 𝑏𝑛 (sin ) (cos ) for n = 1, 2, 3,…
𝐿 𝐿

By superposition and linearity principle, the general solution is the summation of the individual solutions:

𝑛𝜋𝑥 𝑛𝜋𝑡
𝑢(𝑥, 𝑡) = ∑ 𝑏𝑛 (sin ) (cos )
𝐿 𝐿
𝑛=1
(6)

We still have a range of values for bn to find. From IC1 at specific point (midpoint), we can obtain expression at
any point knowing the shape of the string when it is displaced at time t = 0.
u(x,0) Initial Displacement, at time t = 0

x
0 10 20

## For 1  x  20: u(x) = f2(x) = 2 – 0.1x (linear equation y = mc + c)

Based on Equation (6), we can re-write the expression for initial displacement as a function of x:

𝑛𝜋𝑥
𝑢(𝑥, 0) = 𝑓(𝑥) = ∑ 𝑏𝑛 (sin )
𝐿
𝑛=1

## The above is a form of Fourier sine series, which gives

2 𝐿 𝑛𝜋𝑥 2 𝐿
𝑏𝑛 = ∫ 𝑓(𝑥) sin 𝑑𝑥 𝑜𝑟 𝑠𝑖𝑚𝑝𝑙𝑖𝑓𝑦 𝑏𝑛 = ∫ 𝑓(𝑥) sin 𝑘𝑥 𝑑𝑥
𝐿 0 𝐿 𝐿 0

## Solving for bn following the range of validity for f1 and f2:

𝐿 𝐿
𝐿 𝐿
2 2 2 2
𝑏𝑛 = {∫ 𝑓1 (𝑥) sin 𝑘𝑥 𝑑𝑥 + ∫ 𝑓2 (𝑥) sin 𝑘𝑥 𝑑𝑥} = {∫ (0.1𝑥) sin 𝑘𝑥 𝑑𝑥 + ∫ (2 − 0.1𝑥) sin 𝑘𝑥 𝑑𝑥}
𝐿 0 𝐿 𝐿 0 𝐿
2 2

## Integrating by parts separately for the two integrals:

𝐿 𝐿
𝐿
1 2 1
(1) ∫02(0.1𝑥) sin 𝑘𝑥 𝑑𝑥 = [(0.1𝑥) (− cos 𝑘𝑥)] − ∫02 (− cos 𝑘𝑥) (0.1) 𝑑𝑥
𝑘 0 𝑘
𝐿
𝐿 1 𝑘𝐿 0.1 2
= [(0.1 ) (− cos ) − (0)] − [− 2 sin 𝑘𝑥]
2 𝑘 2 𝑘 0
0.1𝐿 𝑘𝐿 0.1 𝑘𝐿
= (− cos )+( 2 sin )
2𝑘 2 𝑘 2

𝐿 1 𝐿 𝐿 1
(2) ∫𝐿 (2 − 0.1𝑥) sin 𝑘𝑥 𝑑𝑥 = [(2 − 0.1𝑥) (− cos 𝑘𝑥)]𝐿 − ∫𝐿 (− cos 𝑘𝑥) (−0.1) 𝑑𝑥
2 𝑘 2 𝑘
2
1 0.1𝐿 1 𝑘𝐿 0.1 𝐿
= [(2 − 0.1𝐿) (− cos 𝑘𝐿) − (2 − ) (− cos )] − [ sin 𝑘𝑥]𝐿
𝑘 2 𝑘 2 𝑘2
2

0.1𝐿
Since L = 20, so the above term (2 − 0.1𝐿) = 0 and (2 − ) = 1 , hence we have:
2

𝐿 1 𝑘𝐿 0.1 0.1 𝑘𝐿
∫𝐿 (2 − 0.1𝑥) sin 𝑘𝑥 𝑑𝑥 = [(𝑘 cos 2
)] − [(
𝑘2
sin 𝑘𝐿) − (
𝑘2
sin
2
)]
2

1 𝑘𝐿 0.1 0.1 𝑘𝐿
= ( cos )−( sin 𝑘𝐿) + ( sin )
𝑘 2 𝑘2 𝑘2 2

𝑛𝜋
Note that we already know 𝑘 = for n = 1, 2, 3 …
𝐿
Now place the results of the integrals into expression for bn:

## 2 0.1(20) 𝑘𝐿 0.1 𝑘𝐿 1 𝑘𝐿 0.1 0.1 𝑘𝐿

𝑏𝑛 = {(− cos )+( sin ) + ( cos )−( sin 𝑘𝐿) + ( sin )}
𝐿 2𝑘 2 𝑘2 2 𝑘 2 𝑘2 𝑘2 2

2 0.1 𝑘𝐿 0.1
= {2 ( sin ) − ( sin 𝑘𝐿)}
𝐿 𝑘2 2 𝑘2

2 0.2𝐿2 𝑛𝜋 0.1𝐿2
= {( sin )−( sin 𝑛𝜋)}
𝐿 𝑛 2 𝜋2 2 𝑛 2 𝜋2

## Knowing sin 𝑛𝜋 = 0 always for integer n = 1, 2, 3 …

Hence
(0.4)𝐿 𝑛𝜋 8 𝑛𝜋
𝑏𝑛 = (sin ) = 2 2 (sin )
𝑛2 𝜋 2 2 𝑛 𝜋 2

## Finally substitute bn into GS in (6) gives:

8 𝑛𝜋 𝑛𝜋𝑥 𝑛𝜋𝑡
𝑢(𝑥, 𝑡) = ∑ (sin ) (sin ) (cos )
𝑛2 𝜋 2 2 20 20
𝑛=1

## Нижнее меню

### Получите наши бесплатные приложения

Авторское право © 2021 Scribd Inc.